Starting at the top: how what happens in the Poudre's Upper Watershed affects all of us below - Kovecses, Jennifer, author (Colorado State University. Libraries, 2014)
In the summer of 2012, wildfires burned over 87,000 acres of the Cache la Poudre watershed. Based on experiences in other parts of Colorado and the west, it quickly became apparent that a wildfire of this scale and intensity could potentially have dramatic negative impacts on the Poudre River - increased runoff, erosion, and flooding would not only change the ecological stability of the forest but also increase the amount of flows, sediment, and debris being delivered to the river. This, in turn, raised concerns about impacts to health of the river, safety on roads, and impacts to our water supply. In the aftermath of the wildfires over 30 natural resource professionals, local government officials, city utilities representatives, local non-profits, scientists, and residents began planning, prioritizing, and implementing post-fire restoration. This informal restoration collaborative has now evolved into a fully-fledged non-profit known as the Coalition for the Poudre River Watershed (CPRW). CPRW's mission is to improve and maintain the ecological health of the Poudre River watershed through community collaboration. While we are still focused on implementing remaining post-fire restoration needs, we are also launching an effort to work with watershed stakeholders to identify other high priority watershed issues such as how to reduce the risk of future catastrophic wildfires in the watershed. Our aim is to develop a community-driven watershed plan for the upper Poudre River.
Presented at the Fall 2014 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Perspectives on the Poudre: Working River/Healthy River", September 23, 2014, 2014, Colorado State University, Fort Collins, Colorado. This fall semester's bi-weekly Seminar and Discussion Series focuses on the Poudre River and its watershed, its ecological needs, and how it is used to supply water for agriculture and urban needs. Presenters will highlight their topics and engage participants in dialogue. The series will culminate in a "world café" - campus and community open dialogue about the Poudre.
Jen grew up playing in lakes and streams in Canada building a life-long interest in aquatic ecosystems and conservation. She pursued this interest in university, completing a Bachelor's of Science in biology and a Master's of Science in aquatic ecology at McGill University. For her Master's thesis, Jen researched the impacts of mining pollution on lakes in northern Quebec. After completing her graduate degree, she continued to pursue her passion for aquatic ecosystems, working on a variety of watershed conservation projects on the shores of Lake Ontario and the coast of British Columbia. While living in California, Jen had the opportunity to work for local non-profits, offering science and policy analysis to help protect water quality and habitat in California's beautiful coastal watersheds. After moving to Colorado in 2011, she began volunteering with Wildlands Restoration Volunteers as a way to get to know some of the amazing places in Colorado. This led to an opportunity to work with Wildlands Restoration Volunteers, managing its post-fire restoration program. When not working, Jen can be found hiking in the mountains or along Colorado's many beautiful rivers
Poster presentation.